Tunable focus lens using electroactive polymer - Ong, You Liang (2018)
The use of lenses has developed over centuries, from the first magnifying glass to the modern-day microscopes. As the demand for small and compact lenses increases, optical lenses with tunable focus ability are intensively researched. The introduction of Dielectric Elastomer Actuator (DEA) into tunable focus lens is one of such breakthrough in technology to achieve the goal of producing compact lenses commercially. However, current type of electrodes used to actuate the tunable focus lens are costly to be produced commercially or are not able to maintain optical transparency of the DEA. This thesis is designed to find a suitable substitute to the costly and non-transparent electrodes used for DEA tunable focus lens. The introduction of PEDOT:PSS as the working electrode as a replacement for the current graphite dust electrode to maintain optical transparency of the DEA and as a cost efficient replacement for indium-tin-oxide (ITO) electrode. In this experiment, PEDOT:PSS electrode and Timrex KS6 graphite dust electrode will undergo identical high voltage actuation using encapsulated gels lens of identical encapsulation volume. Their performance capabilities will be compared through the change in Radius of Curvature and Magnification Factor. Preliminary results show almost identical rate of change of DEA actuation without encapsulation lens by both electrodes, and a 7% difference in performance in the change of Radius of Curvature. The difference in performance may be attributed to the stiffness of the Gel lens and the physical properties of PEDOT:PSS and Timrex KS6 graphite electrode.